Long-term straw return with moderate nitrogen levels reshapes soil bacterial communities in a vertisol - Guo, Zichun; Qian, Rui; Li, Wei; Ding, Tianyu; Gao, Lei; Peng, Xinhua (Frontiers in Microbiology, 2025)
IntroductionIncorporating straw into the soil is a sustainable practice that can mitigate some of the adverse effects of excessive N fertilization on soil structure degradation and microbial diversity reduction.MethodsThis objective of this study was to determine the combined effects of straw management (straw return and straw removal) and N fertilization (0, 360, 450, 540, 630, and 720 kg N ha−1 yr.−1) on crop yields, soil properties, and soil microbial communities in a long-term wheat-maize cropping system.Results and discussionThe results showed that moderate N application (N450–N540) with straw return optimized wheat (283.5 kg ha−1) and maize (346.5 kg ha−1) yields, whereas higher N fertilization (N630, N720) led to soil acidification (pH decline of 0.51–1.67 units), irrespective of straw management. Straw return increased soil organic carbon (SOC), total nitrogen (TN), nitrate (NO3−-N), and available potassium (AK), but decreased ammonium (NH4+-N). Bacterial diversity increased at moderate N rates but decreased at higher N rates. Fungal diversity was generally higher under straw removal, with Chaetomiaceae increasing under straw return, whereas Mortierellaceae and Trichocomaceae declined at high N levels. The Mantel test showed a strong correlation between soil pH and bacterial diversity, while fungal composition was influenced by SOC, TN, and NO3−-N. Partial Least Squares Path Modeling (PLS-PM) demonstrated that N fertilization directly and indirectly increased wheat yield through improved soil properties, while straw return enhanced bacterial diversity, indirectly supported wheat yield. This study highlights the importance of balanced N fertilization and straw incorporation in maintaining bacterial community structure, fertility, and long-term crop productivity in intensive cropping systems on Vertisol.